The effect of stretching on sports performance and the risk of sports injury: A review of the literature - Gremion, D. (Schweizerische Zeitschrift für Sportmedizin und Sporttraumatologie, 2005)
It is generally accepted that increasing the flexibility of a muscle-tendon unit allows a better performance and decreases the number of injuries. Stretching is regularly included in warm-up and in cooling- down exercises. However, contradictory findings have been reported in the literature. Since 1980, several authors have suggested that stretching has a beneficial effect on injury prevention. In contrast, since 1990, clinical evidence suggests that stretching not only does not prevent injuries, but can also decrease the level of performance. Some part of these contradictions can be explained by the various sports activities and the eclectic group of athletes studied. Sports activities requesting an increased flexibility, such as gymnastic, dancing, ice skating or diving, necessitate pre-exercise stretching to optimize the level of performance. In contrary, for sports with slow stretch-shortening cycle (SSC) such as jogging or cycling, there is no scientific data showing a positive effect of stretching on performance, injury prevention and recovery. On the basis of the literature this article reviews the interest of the pre- and post-exercise stretching on the different modalities such as range of motion improvement, injury prevention and capacity of recovery.